Development Of A User Friendly Liquid Level Measuring System. - Rehman, Mahfoozur; Saad, M R; Abdullah, Mohd Zaid (2008)
The paper deals with the theory, design, fabrication and testing of a sensor and associated measuring system, which can be used for direct display of levels of conducting as well as non-conducting liquids.